The Relative Age Effect on Competition Performance of Spanish International Handball Players: A Longitudinal Study - de la Rubia, Alfonso; Lorenzo, Alberto; Bjørndal, Christian Thue; Kelly, Adam Leigh; García-Aliaga, Abraham; Lorenzo-Calvo, Jorge (Frontiers in Psychology, 2021)
Competitive success is the ultimate objective of elite professional sport organisations. Relative age effects (RAE) impact athlete selection processes in the short and long-term. The aims of this study were: (i) examine the presence of RAE by gender, competitive level, and playing position, as well as evaluate the impact of RAE on individual and collective competition performance; and, (ii) analyse the impact of RAE on the evolutionary trends of individual performance in international competitions throughout 16 seasons in Spanish handball (2005-2020). The sample included 631 Spanish handball players (male: n = 359; female: n = 272). A Chi-square goodness-of-fit test and subsequent odds ratio calculations were used to assess whether a skewed birthdate distribution occurred. A one-way analysis of variance (ANOVA) of independent measures was used to examine the statistical parameters by birth quartiles (Q). A Hopkins sheet was used to compare individual performance trends between relatively older and relatively younger players. The results revealed a prevalence of RAE in the male formative categories (p < 0.001), as well as the male and female senior categories (p < 0.05). By position, RAE especially affected the ‘centre-back’ in the male formative (p < 0.01) and senior categories (p < 0.05). No significant relationship between RAE and individual performance was found in male formative categories, while an impact of RAE on the ‘minutes played’ was detected in the female senior category (p < 0.05). With regard to collective performance, a higher number of relatively older handball players was observed in the best ranked teams in the male formative categories and in the quarter-final teams in the female formative categories (p < 0.05). Among the male players, relatively older players spent more minutes on the court than relatively younger players, although this advantage dissipated over time and did not lead to better performance. Among the female players, relatively younger players were found to perform better as the level of competitive handball increased. These findings are important for talent identification and development policy in elite sport institutions by demonstrating the many unintended consequences of selections to international competitions at the youth level.